Transferring prisoners within the EU framework: its cosmopolitan reflections and existing European detention norms - Deruiter, Rebecca (2015)
A perverse side-effect of our interconnected world is that also crime crosses more and more borders. As a result, judicial cooperation in criminal matters is crucial before and after a criminal sentence. The increased global connectivity also gave rise to new paradigms in social sciences. As such, the paradigm of cosmopolitanism has been researched extensively in social sciences but has been largely neglected in criminology. By analyzing case law, European detention norms and EU legal instruments the submission critically evaluates cosmopolitanism in the area of EU judicial cooperation in criminal matters and more specifically to the transfer of prisoners. Cosmopolitanism is perfectly reflected in the mutual recognition principle as the cornerstone to develop the EU area of freedom, security and justice, based on notions of equivalence and trust. This principle is justified because every member state signed the European Convention of Human Rights and is a party of the EU Charter on Human Rights. On the other hand, reality revealed that mutual recognition is not absolute and mutual trust cannot be blind. An IRCP study, published in 2011, highlighted the various and often detrimental material prison conditions in different member states. These variances undermine the assumed mutual trust between member states although European detention norms - such as the European Prison Rules and CPT reports’ already exist. These norms aren’t legally binding and are still considered as “soft law”, simultaneously they gain importance due to increased reference in the ECtHR judgments. The cosmopolitan outlook by the member states related to the transfer of prisoners is in this submission highlighted as being both problematic and promising. Hereby it appears as if the EU rhetoric being a “unity in diversity”, by applying mutual recognition, is dominantly used to accommodate member states purposes rather than giving a central role to the individual